IN MODERN LINGUISTICS, THE STUDY OF CONTENT RELATIONS AT THE SYNTACTIC LEVEL IS CONCERNED (Scientific journal of the Fergana State University, 2025)
This article presents theoretical ideas about the in-depth study of the content Relations at the syntactic level by large scientists, about the content relations between parts of the main syntactic units, as well as about the peculiarities of the semantic relations that occur between the components of supersyntactic wholes, and reacted to them.